Cesación del apremio personal en materia de alimentos en días no laborables - Piedra Ochoa, Rebeca Abigail (2023)
The cessation of personal restraint in matters of maintenance refers to the cessation of the measure of deprivation of liberty that was imposed on a maintenance debtor for failure to comply with his obligation. The General Organic Code of Processes establishes in its regulations that one of the reasons for which the personal restraining order may cease is that the imposed obligation is fulfilled, that is, that the obligor pays his debt. This research work focuses on the application of the measure of cessation of personal restraint on non-working days, since, if the obligor pays his debt, for example on a Saturday, he cannot immediately recover his freedom in accordance with the law. because the Family, Women, Children and Adolescents Judges who know the maintenance processes do not work these days, having to wait until Monday and in case there is a holiday the next working day for the Judge to take cognizance of the case and issue the release ticket. The current regulations do not contemplate this legal problem, which produces a lack of regulatory clarity and the violation of a series of rights and principles towards the obligor by keeping him deprived of his freedom until the competent Judge takes office, being that after the development This investigation proposes to grant the Judges on duty the exclusive competence to address and resolve cases of cessation of personal constraint on non-working days, and thus address the situation in a timely and effective manner.